Intelligent nanomaterials : processes, properties, and applications - Tiwari, Ashutosh (Wiley ; Scrivener Publishing, 2012)
"Smart and intelligent nanomaterials are currently in sharp focus in materials research as their properties are increasingly becoming more understood. This large and fairly comprehensive volume includes thirty chapters divided into four main areas: Inorganic materials, organic materials, composite materials, and biomaterials. It covers the latest research and developments in smart nanomaterials: processing, properties, and applications. Included are molecular device materials, biomimetic materials, hybrid-type functionalized polymers-composite materials, information-and energy-transfer materials, as well as environmentally friendly materials"-- Nakladatelská anotace
Keywords: nanomateriály; kompozitní materiály; biologické materiály; anorganické materiály; materiálové inženýrství; materiálové technologie; nanostructure materials; composite materials; biological materials; inorganic materials; materials engineering; material technologies; kolektivní monografie; collective monographs